THE INFLUENCE OF MINERAL NUTRITION ON SOYA PRODUCTIVITY - Barabolia, O. V.; Naidon, M. Yu.; Kononenko, S. M.; Korovnichenko, S. H. (Scientific Progress & Innovations, 2020)
The relevance of combining of phosphate-potassium and nitrogen fertilizers in soybean fertilization sys-tem in order to implement its genetic potential has been substantiated in the article. The aim of the study was to establish the optimal reasonable rates of nitrogen fertilizers. The research to study the effectiveness of different quantities of nitrogen fertilizers during soybean cultivation was performed in a temporary experi-ment with three randomized variant placements. The following mineral fertilizers were used: ammonium ni-trate, granular superphosphate and potassium chloride. Phosphate and potassium fertilizers were applied at basic tillage, and nitrogen – at pre-sowing soil cultivation in the spring. Carrying out field experiments, se-lecting plant and soil samples, observing and studying were conducted according to the recommendations and methodical instructions of recent years. The research results have shown that applying nitrogen fertiliz-ers is the main factor influencing the realization of the genetic potential of soybean productivity and reduces moisture consumption on the formation of yield unit. The application of nitrogen fertilizers (N60) and (N90) at phosphate-potassium background (Р60К60) allows to reduce moisture consumption on the formation of yield unit by 34–39 % as compared with the variant without fertilizers. The application of nitrogen fertilizers (N30-90 at the background of P60K60) increases the content of nitrate and ammonium nitrogen in soil layers 0–20 and 20–40 cm in the range from 1.1 to 4.7 %, respectively. Mineral fertilizers had a very positive effect on biometric indicators of soybean plants. The variants, in which nitrogen fertilizers were used at the back-ground of phosphate-potassium fertilizers, were the best ones. There was a tendency to improve the corre-sponding indicators at increasing the rates of nitrogen fertilizers. On the average, the highest yield of soy-bean seeds, over the years of the research was 25.5 hundredweight/ha, and it was formed in the variant with applying nitrogen at a rate of N90. The increase, as compared with the variant without fertilizers, was 7.6 hundredweight/ha or 42 %. The difference according to the given indicator on the variants, in which N30 and N60 were applied, was 1.6 hundredweight/ha. Positive effect after applying mineral fertilizers on soybean seed quality indicators was revealed. The maximum protein content in soybean grain (38.2 %) was found in the variant with applying nitrogen fertilizers at a rate of 90 kg/ha of active substance. The same variant was characterized by its highest yield per unit area – 9.7 hundredweight/ha. The highest fat content (22.0 %) in soybean grain was found in the variant without fertilizers. Improving the conditions of mineral nutrition due to applying nitrogen fertilizers contributed to reducing its content by 20.1 %.